2015
DOI: 10.1007/s10753-014-0103-z
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Serum B7-H3 Levels in Patients with Ankylosing Spondylitis

Abstract: This study aimed to investigate molecule B7-H3 expression profiles of patients with ankylosing spondylitis (AS) and the clinical significance of B7-H3 in the pathogenesis of AS. Serum B7-H3 levels were measured by ELISA in patients with AS and healthy controls. The expression of B7-H3 protein and mRNA on CD14+ monocytes of peripheral blood mononuclear cells (PBMCs) and serum levels of T cell-associated cytokines were also analyzed. The serum B7-H3 levels in AS patients were significantly lower than in healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 17 publications
1
4
1
Order By: Relevance
“…This suggests that mB7‐H3 may be cleaved to form sB7‐H3, this cleavage may be result in lower expression on the cellular membrane in AITD. Supporting this hypothesis, sB7‐H3 has been found in serum 13 and sB7‐H3 level has been associated with autoimmune diseases such as MS, AS, and RA 14–16 . In this study, however, we did not find any association between plasma sB7‐H3 levels and AITD development (Figure 2).…”
Section: Discussionsupporting
confidence: 42%
See 2 more Smart Citations
“…This suggests that mB7‐H3 may be cleaved to form sB7‐H3, this cleavage may be result in lower expression on the cellular membrane in AITD. Supporting this hypothesis, sB7‐H3 has been found in serum 13 and sB7‐H3 level has been associated with autoimmune diseases such as MS, AS, and RA 14–16 . In this study, however, we did not find any association between plasma sB7‐H3 levels and AITD development (Figure 2).…”
Section: Discussionsupporting
confidence: 42%
“…sB7‐H3 is cleaved from mB7‐H3 13 . Both mB7‐H3 and sB7‐H3 are associated with various autoimmune diseases such as rheumatoid arthritis (RA), multiple sclerosis (MS) and ankylosing spondylitis (AS) 14–16 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cellular role of B7-H3 remains controversial until now [10] . Earlier studies, including our previous study, have shown that B7-H3 is associated with autoimmune diseases, such as RA, myasthenia gravis, ankylosing spondylitis, and systemic lupus erythematosus [11][12][13][14] . The expression of B7-H3 on peripheral blood monocytes of RA patients is closely related to clinical manifestations, although the mechanism of action of B7-H3 in RA remains unclear.…”
Section: Introductionmentioning
confidence: 66%
“…Of note, the inhibitory function of B7‐H3 on T‐cell proliferation, activation and cytokine production was also reported in recent studies (Wang et al., 2016; Suh et al., 2003). It was found that serum B7‐H3 levels in AS were significantly lower than healthy individuals, and the reduced serum B7‐H3 levels were negatively correlated with AS Disease Activity Score (ASDAS), implying the potential role of B7‐H3 in AS (Yan et al., 2015).…”
Section: Introductionmentioning
confidence: 99%